Predictors of lead break during transvenous lead extraction. Issue 3 (15th March 2021) - Morita, Junji; Yamaji, Kyohei; Nagashima, Michio; Kondo, Yusuke; Sadohara, Yohei; Hirokami, Jun; Kuji, Rei; Korai, Kengo; Fukunaga, Masato; Hiroshima, Kenichi; Ando, Kenji; Goya, Masahiko
Abstract: Background: The incidence, predictors, and clinical impact of lead break during transvenous lead extraction (TLE) were previously unknown. Methods: We included consecutive patients who underwent TLE between September 2013 and July 2019 at our institute. Lead break during removal was defined as lead stretching and becoming misshapen, as assessed by fluoroscopy. Results: A total of 246 patients underwent TLE for 501 leads. At a patient level, complete success was achieved in 226 patients (91.9%). At a lead level, 481 leads (96.0%) were completely removed and 101 leads (20.1%) were broken during the procedure. Of 392 identified pacemaker leads, 71 (18.3%) were broken during the TLE procedure. A multivariable analysis confirmed high lead age (odds ratio [OR] 1.12, 95% confidence interval (CI) 1.07‐1.17; P  < .001), passive leads (OR 2.29 95% CI 1.09‐4.80; P  = .028), coradial leads (OR 3.45 95% CI 1.72‐6.92; P  < .001), and insulators made of nonpolyurethane (OR 2.38 95% CI 1.03‐5.26; P  = .04) as predictors of lead break. Broken leads needed longer procedure times and were associated with a higher rate of cardiac tamponade. Conclusions: Lead age, coradial bipolar leads, passive leads, and leads without polyurethane insulation were predictors of lead break and could increase the difficulty of lead extraction. Abstract : The extraction of cardiac implantable electronic device leads due to infections, malfunctions, and recalls is common, and can lead to complications such as lead break resulting in incomplete lead removal and cardiac tamponade. We found that older lead age, co‐radial leads, passive leads, and non‐polyurethane leads were independent predictors of lead break during extraction. These findings will guide clinicians to make appropriate choices of procedure and take greater care when these risk factors are present.